Apertures with Laval Nozzle and Circular Orifice in Secondary Electron Detector for Environmental Scanning Electron Microscope (Advances in Military Technology, 2022)
Environmental scanning electron microscopes offer wide possibilities for the exploration of various types of specimens, especially non-conductive and wet specimens containing different material phases. The evaluation of pressure on the secondary electrons trajectory is one of the important parameters in design of scintillation detector of secondary electrons. The final process is influenced by the size and the shape of the apertures used to separate areas with different pressure gradient. This article is focused on the comparison of the aperture with circular orifice and aperture with Laval nozzle.
Keywords: aperture; Laval nozzle; circular orifice; pressure; detector; Mach number; flow; trajectory of secondary electrons